Proceedings new towns and development plans, economic, management, traffic and transportation (Tehran, Iran : Ministry Housing and Urban Development, 2007)
v.1--New towns experiences in Iran and around the world--v.2 Identity in new towns inNew towns and development plans, economic, management, traffic and transportation new tows--v.3 New towns and development plans, economic, management, traffic and transportation